2021
DOI: 10.1002/micr.30802
|View full text |Cite
|
Sign up to set email alerts
|

Pedicled fibular transfer for biologic knee extensor tendon reinsertion following proximal tibial resection in pediatric osteosarcoma: Long‐term outcomes

Abstract: Introduction: Proximal tibial sarcoma resections result in a reconstructive challenge, necessitating joint and extensor mechanism reconstruction. The gait and functional outcomes for children reconstructed with a combination of megaprosthesis and pedicled fibular flap for extensor mechanism reconstruction, are presented.Methods: Four patients, aged 11-18 years old, were available for comprehensive analysis. The proximal tibial osteosarcoma was resected, and the reconstructive technique involved a megaprosthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…A recent review of our patients showed excellent medium‐ and long‐term outcomes, but an incidence of skin wound edge breakdown of 43% in the short term. Seven patients with adequate follow‐up had undergone this specific procedure, but three of those required early debridement and skin grafting onto the underlying gastrocnemius flap 3 . Whilst this delayed the recommencement of chemotherapy to a short extent, to our knowledge there have not been oncological repercussions from these delays.…”
Section: Figmentioning
confidence: 97%
See 1 more Smart Citation
“…A recent review of our patients showed excellent medium‐ and long‐term outcomes, but an incidence of skin wound edge breakdown of 43% in the short term. Seven patients with adequate follow‐up had undergone this specific procedure, but three of those required early debridement and skin grafting onto the underlying gastrocnemius flap 3 . Whilst this delayed the recommencement of chemotherapy to a short extent, to our knowledge there have not been oncological repercussions from these delays.…”
Section: Figmentioning
confidence: 97%
“…The Alfred Hospital in Melbourne has the highest ECMO caseload in Australia. 3 As such, this heterogenous and complex group of patients form an important proportion of acute referrals to our vascular surgery department. Despite increasing worldwide experience in managing patients on ECMO, the appropriate algorithm for diagnosis and investigation of LLI for patients on ECMO is still poorly defined.…”
Section: Introductionmentioning
confidence: 99%